Tolerância e nodulação de soja (Glycine max (L.) Merril), cultivada em dois substratos e submetida a quatro doses de metribuzin - Pinheiro de Moraes, Rita de Cássia; Fernandes Lopes, Nei; Monteiro da Silva, Eldo Antônio; do Valle Rodrigues, Joaquim Joel (Revista Ceres, 2025)
The effect of metribuzin rates 00, 0.3. 0.6 and 0.9 kg aiha-1 on the toxicity. tolerance and nodulation of soybean cv. Parani cultivated on two different substrata (soil + sand and soil) and inoculate with Bradyrhizobium japonicum, was studied under greenhouse conditions at Viçosa, MG, Brazil.